Mechanical and wear behaviour of AA6061/SiC composites fabricated by powder metallurgy method. (2020) - Dhanashekar, M.; Loganathan, P.; Ayyanar, S.; Mohan, S.R.; Sathish, T.
Abstract: This paper reports the mechanical properties and wear behaviour of AA6061/Silicon Carbide (SiC) composites fabricated through powder metallurgy routine. Green uni-axially pressed compacts in the range of 350 MPa was sintered at temperatures in the range of 610–640 °C. The microstructures of AA6061/SiC composites interfaces were characterized by Optical Microscope and mechanical properties were evaluated by Vickers hardness tester and compression test. The test results revealed that increase in hardness and compressive strength of the composite was evidenced with increasing reinforcement level. The fabricated composites showed a good sintering response and the density achieved was maximum. Optimal microstructure showed homogeneous distribution of reinforcement particles in the composites. The wear rate of composites gets decreased with increased wt% of SiC due to formation of mechanical mixed layer (MML) and resist the direct contact of mating parts.